Building Empathy in Young Children Using Augmented Reality - Zamin, N; A. Khairuddin, F; R. A. Rambli, D; N. M. Ibrahim, E; S. A. Soobni, M (International Journal of Engineering and Technology, 2018)
Empathy is the feeling that a person can step out virtually from his/her own world and enter the internal world of another person.  In simple notation, empathy means the ability to ‘feel with’ other people, to sense what they are experiencing.  Empathy is different than sympathy.  It is a hard-wired capacity many of the people today is lacking. A psychological study has found that many people are suffering from Empathy Deficit Disorder (EDD). EDD gets severe by the increasingly polarized social and political culture especially in the under developed countries.  Lack of empathy and social wellness can be very damaging to the families, organizations and countries. This research investigates how compassion can be trained as a coping strategy to build social wellness using augmented reality on our young generations.  Smart and empathic citizens are the key to the success of Industrial Revolution (IR) 4.0.